Hyaluronic Acid Can be a New Plant Growth Regulator for Hybrid Cymbidium Micropropagation - Kaewjampa, Naruemol; Shimasaki, Kazuhiko; Nahar, Syeda Jabun (Plant Tissue Culture and Biotechnology, 2012)
Present authors investigated the effect of two biopolymer hyaluronic acid (HA9) and chitosan (Chitosan H), and N6-benzyladenine (BA) supplemented with modified MS on organogenesis in protocorm-like bodies (PLBs) of a Cymbidium cultivar. The percentages of PLB formation from cultures showed 100 % in all treatments except for control (82.7%), 0.1 mg/l HA9 (93.3%) and 10 mg/l Chitosan H (93.3%) treatments. Addition of 0.1 mg/l HA9 to culture medium was highly efficient for PLB multiplication. Both 10 mg/l HA9 and 1.0 mg/l BA significantly increased the number of shoots in cultures. The maximum percentage of shoot (100%) was obtained at 1.0 mg/l chitosan H. Increase in fresh weight showed higher values at BA treatments. Information gained from this study shows that hyaluronic acid (HA9) which is new additive for plant tissue culture act as growth regulator for hybrid Cymbidium micropropagation. DOI: http://dx.doi.org/10.3329/ptcb.v22i1.11261 Plant Tissue Cult. & Biotech. 22(1): 59-64, 2012 (June)